Penerapan Kebijakan Pajak Semasa Pandemi Covid-19,Kualitas Pelayanan Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor: Studi Kasus Di Kantor Bersama Samsat Ilir Barat l Palembang - Anita Sari; Emilia Gustini Emilia Gustini; R.M.Rum Hendarmin (Jurnal Bisnis, Manajemen, dan Ekonomi, 2021)
This study aims to examine the implementation of tax policies during the COVID-19 pandemic, service quality, and tax sanctions on motor vehicle taxpayer compliance (a case study in the joint office of Samsat Ilir Barat I Palembang). Interviews and questionnaires were carried out in the data collection process. The sampling method was simple random sampling and obtained 100 respondents. Furthermore, the collected data were analyzed using multiple linear regression. The result evinces that tax policy, service quality, and tax sanctions had a positive effect on taxpayer compliance. Furthermore, the results of the study support previous research which proves that tax policy, service quality, and tax sanctions simultaneously have a positive effect on motor vehicle taxpayer compliance. This research is expected to be useful for the SAMSAT Ilir Barat 1 Palembang office to increase compliance with motor vehicle taxpayers who must pay attention to tax policies, service quality, and tax sanctions